The effect of low nanosilica content on the breakdown strength of low density polytechylene [electronic resource] - Joeyride Rowenn Jom, 1993-, author (2016)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik)) - Fakulti Kejuruteraan Elektrik, 2016